Preparation method of multi-component structure gradient material and gradient structure
By designing a single-component wafer and a regulatory structural element of density gradient in a multi-component structure gradient material, the dual gradient regulation of material components and structural characteristics is achieved, the problem of narrow impedance range in the prior art is solved, and the mechanical properties and stability of the material are improved.
Patent Information
- Application Number
- CN202411809821.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-12-10
AI Technical Summary
The prior art has failed to effectively solve the structure-effect relationship between multi-path loading waveform, wide stress and strain rate regulation range, and the stress and strain rate and controllable loading waveform, resulting in a narrow impedance range of structural gradient materials.
Through the reasonable configuration of single-component wafer design with different density in the component gradient model and the consistent size of the regulatory structural primitives in the structural gradient model, the dual gradient control of material components and structural characteristics is realized. The component and structural gradient models are constructed using simulation software, and the multi-component gradient structure is prepared through 3D printing technology.
The impedance adjustable range of structural gradient materials is improved, the mechanical properties and stability of the structure are improved, and the molding quality and manufacturing efficiency are ensured by precise control of 3D printing parameters, and the bonding strength of the material interface is enhanced.
Smart Images

Figure CN119502331A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of functional gradient structure design, and in particular to a preparation method of a multi-component structural gradient material and a gradient structure. Background Art
[0002] Materials in key areas such as national defense security (advanced weapons, artillery) and high-end manufacturing (cutting tools) need to withstand high stress (1-100 GPa), wide strain rate (10 4 ~10 6 / s) of extreme service load conditions, accurately understanding and mastering the evolutionary behavior of materials in extreme service environments is crucial to improving service safety, developing advanced strategic weapons, and establishing a material genetic engineering database. The dynamic high-pressure technology used to simulate extreme service environments of materials is mainly impact loading technology and Hopkinson bar (SHPB) technology. The former uses homogeneous flying pieces, which leads to high impact pressure and large strain rate (700GPa, 10 8 / s, while the latter has a lower loading strain rate (10 -4 ~10 0 / s). The controllable loading technology is to change the wave impedance of the homogeneous flying piece from low to high gradient along the flight direction during impact loading, and hit the target to generate a loading wave with slowly rising pressure. It can economically and effectively simulate the extreme service load environment of key materials in a laboratory environment. It has the advantages of large time and space scales, relatively controllable wavefronts, high measurement accuracy (absolute measurement), and low technical cost. It has become the mainstream experimental technology for achieving different loading stresses and strain rates in the world.
[0003] The Chinese patent with publication number CN118269354A discloses a gradient structure and preparation method for realizing controllable stress-strain rate loading, which includes the following steps: constructing a dielectric substrate model and a plurality of identical structural primitive models through simulation software; arranging a plurality of said structural primitive models on the upper surface of said dielectric substrate model in a preset arrangement manner, thereby forming a gradient structure STL model, wherein the cross-sectional area of said structural primitive model gradually increases from the direction away from said dielectric substrate model to the direction close to said dielectric substrate model; preprocessing said gradient structure STL model to obtain a gradient structure slice model, wherein said gradient structure slice model includes a plurality of two-dimensional slices of the same thickness; preparing a surface density gradient structure corresponding to said gradient structure slice model based on printing parameters and surface projection micro-stereolithography technology. However, the above scheme does not take into account the multi-path loading waveform of the component gradient model, the structure-activity relationship between the gradient structure with a wide stress-strain rate control range and the stress-strain rate and controllable loading waveform, resulting in a single impedance of the structural gradient material and a narrow impedance range. Therefore, it is very necessary to provide a preparation method and gradient structure of a multi-component structural gradient material to improve the impedance controllable range of the structural gradient material. Summary of the invention
[0004] In view of this, the present invention proposes a preparation method and gradient structure of a multi-component structural gradient material. Through the design of single-component discs with different densities in the component gradient model and the reasonable configuration of the control structural primitives with the same size in the structural gradient model, the dual gradient control of material components and structural properties is achieved, thereby improving the impedance control range of the structural gradient material.
[0005] The present invention provides a method for preparing a multi-component structural gradient material, the method comprising:
[0006] Constructing a component gradient model and a structural gradient model by simulation software, wherein the component gradient model includes a plurality of single-component discs with different densities, and the structural gradient model includes a plurality of regulatory structural primitives with the same size;
[0007] Arranging a plurality of the regulatory structural primitives in a preset arrangement on the upper surface of the component gradient model to form a multi-component gradient structural model, wherein the cross-sectional area of the structural primitive model gradually increases from a direction away from the component gradient model toward a direction close to the component gradient model;
[0008] Based on printing parameters and 3D printing technology, a multi-component gradient structure corresponding to the multi-component gradient structure model is prepared, wherein the printing parameters include the single-component disc layer thickness, exposure intensity and printing speed.
[0009] On the basis of the above technical solution, preferably, based on printing parameters and 3D printing technology, a multi-component gradient structure corresponding to the multi-component gradient structure model is prepared, specifically including:
[0010] Using an FDM device to print a component gradient structure corresponding to the component gradient model, wherein the nozzle temperature of the FDM device is set to 200-230°, the printing speed of the FDM device is set to 25-40 mm, and the layer thickness of the single-component disc is set to 0.05-0.2 mm;
[0011] The structure gradient corresponding to the structure gradient model is printed on the upper surface of the component gradient structure by using an SLA device, wherein the light wavelength used by the SLA device is 355nm, the layer thickness of the printing of the SLA device is set to 0.01-0.05mm, and the exposure intensity of the SLA device is set to 20-100mW / cm 2 ;
[0012] The prepared multi-component gradient structure was cleaned and placed under a light intensity of 60-80 mW / cm 2 The secondary curing is completed by irradiating in a curing box for 15 to 30 minutes.
[0013] On the basis of the above technical solution, preferably, the Hill function and impedance change function of the control structure primitive are:
[0014] f(x)=f(0)+R×(x h ) / (x h +K h )
[0015] Z(x)=k×ρ×C b ×[f(x)] 2
[0016] Wherein, f(x) represents the Hill function of the control structure unit, x represents the thickness coordinate of the structure gradient material from the low-density end, f(0) represents the minimum radius of the tip of the actual prepared structure unit, R represents the control impedance change range, K represents the proportional coefficient of the impedance change span, h represents the Hill coefficient of the control impedance change form, Z(x) represents the impedance change function at the position x thickness from the initial layer, ρ represents the material density at the position x thickness from the initial layer, C b represents the sound velocity at constant pressure at a position x thickness away from the initial layer, and k represents the proportional coefficient of impedance change.
[0017] More preferably, the single-component disc is prepared by filling a resin-based composite material with metal particles of different contents, and the particle size of the metal particles is 1 to 10 μm.
[0018] More preferably, the metal particles are copper particles, and the resin-based composite material is PMMA.
[0019] More preferably, the mass fraction of the copper particles is any one of 10wt.%, 25wt.%, 40wt.% and 60wt.%, and the mass fraction of PMMA is any one of 90wt.%, 75wt.%, 60wt.% and 40wt.%.
[0020] More preferably, the thickness of the single-component disc is 50-400 μm, and the density of the single-component disc is 1.3-4.5 g / cm 3 .
[0021] More preferably, the component gradient model comprises five layers of single-component discs with different densities, and a plurality of the single-component discs are stacked in order from small to large density to obtain a component gradient model with uniformly increasing component density.
[0022] More preferably, the regulatory structural unit comprises any one of polyurethane acrylic resin, polyester acrylic resin and amino acrylic resin, and the volume density of the regulatory structural unit is 0 to 1.3 g / cm3 .
[0023] The present invention also provides a gradient structure of a multi-component structural gradient material prepared by the above-mentioned preparation method.
[0024] The preparation method and gradient structure of a multi-component structure gradient material provided by the present invention have the following beneficial effects compared with the prior art:
[0025] (1) Through the design of single-component discs with different densities in the component gradient model and the reasonable configuration of regulatory structural elements of the same size in the structural gradient model, dual gradient regulation of material components and structural properties is achieved, solving the problems of single structure and limited controllable range caused by regulating the structure through structural parameters, thereby improving the impedance control range of the structural gradient material. At the same time, the gradual design of the cross-sectional area of the structural element effectively improves the stress concentration phenomenon and improves the mechanical properties and stability of the structure. By precisely controlling 3D printing parameters such as layer thickness, exposure intensity and printing speed, the molding quality and manufacturing efficiency are ensured, and the material interface bonding strength is enhanced.
[0026] (2) Through the organic combination of the Hill function and the impedance change function, a quantitative relationship between structural parameters and performance was established. The Hill function achieves a continuous and controllable change in the size of the structural element by adjusting the Hill coefficient h, the proportional coefficient K and the R value. The impedance change function takes into account the influence of material density and sound velocity and achieves precise regulation of impedance. This multi-parameter coordinated control method not only provides theoretical guidance for structural design and a mathematical basis for performance prediction, but also has good parameter adjustability and engineering applicability.
[0027] (3) By adopting a multi-level ratio combination of copper particles with a particle size of 1 to 10 μm and PMMA resin-based composite materials, precise thickness control and density gradient regulation of single-component wafers are achieved. Micron-sized copper particles ensure good dispersibility and interface bonding, and the PMMA resin matrix provides excellent processing performance and coating properties. The multi-level ratio optimizes the interfacial stress distribution, which not only realizes the continuous and controllable change of material properties, but also has practical advantages such as controllable process flow, predictable performance, and reasonable cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0029] Figure 1 A schematic flow chart of a method for preparing a multi-component structural gradient material provided by the present invention;
[0030] Figure 2 A schematic diagram of the structure of the multi-component gradient structure model provided by the present invention;
[0031] Figure 3 A schematic diagram of mathematical function control with different wave impedance distribution indexes provided by the present invention;
[0032] Figure 4 A schematic diagram of the structure of a multi-dimensional arrangement form for achieving controllable stress-strain rate provided by the present invention;
[0033] Figure 5 A schematic diagram of the regulation effect of achieving the stress-strain rate range provided by the present invention;
[0034] Figure 6 Impedance distribution diagram for realizing stress strain rate range provided by the present invention;
[0035] Figure 7 A microstructure diagram of the gradient structure provided by the present invention;
[0036] Figure 8 A tensile strength curve diagram for achieving a stress-strain rate range provided by the present invention. DETAILED DESCRIPTION
[0037] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] Before introducing the embodiments of the present invention, some terms and their abbreviations involved in the embodiments of the present invention are first defined and explained.
[0039] Gradient materials are materials with gradually changing properties, whose properties or components change continuously along one or more directions. This gradual change can include changes in the chemical composition, physical properties, structure or morphology of the material. The design of gradient materials aims to achieve more precise control and optimization of the material's performance to meet the needs of specific applications. Gradient materials can be classified according to the properties of the change, which include but are not limited to mechanical properties, optical properties, thermal conductivity properties, electromagnetic properties, etc. The following are some common types of gradient materials: Mechanical gradient materials: Its hardness, strength or toughness gradually changes within the material, thereby optimizing the local stress distribution and improving the wear resistance and fatigue resistance of the material. Thermal gradient materials: Its thermal conductivity gradually changes along a specific direction, which can play an important role in thermal management, such as in the manufacture of thermal barrier coatings or in thermal energy conversion devices. Optical gradient materials: Its refractive index or transparency gradually changes in space, and can be used to manufacture optical components such as lenses, prisms, and optical waveguides. Chemical gradient materials: Its chemical composition or surface treatment gradually changes within the material, and can be used in surface coatings, biomedical materials and other fields.
[0040] FDM technology is an additive manufacturing process based on the melting, extrusion and layer-by-layer deposition of thermoplastic materials. It heats the filamentary thermoplastic material to a molten state, deposits it layer by layer along a preset path through a precisely controlled nozzle system, and then cools and solidifies to form a three-dimensional solid model. As one of the earliest 3D printing technologies, FDM has become the most popular 3D printing technology due to its advantages such as simple equipment structure, easy operation and maintenance, and a wide range of material selection. It plays an important role in product prototype development, education and training, small batch production and other fields.
[0041] Stereolithography (SLA) technology: SLA technology is based on the principle that photosensitive resin undergoes photopolymerization reaction under light of a specific wavelength. By controlling the laser beam or projection light source to selectively irradiate the liquid photosensitive resin, it solidifies in a specific area and eventually forms a three-dimensional solid model by stacking layer by layer. As one of the earliest technologies in the field of additive manufacturing, SLA has the advantages of high molding accuracy, good surface quality, and the ability to realize complex structures. With the continuous advancement of light source technology, resin materials and control systems, especially the introduction of DLP (digital light processing) technology, SLA equipment has achieved significant improvements in molding efficiency, material properties and application scope.
[0042] The present invention discloses a method for preparing a multi-component structure gradient material, referring to Figure 1 The method includes steps S1 to S3.
[0043] Step S1, constructing a component gradient model and a structural gradient model through simulation software, wherein the component gradient model includes a plurality of single-component discs with different densities, and the structural gradient model includes a plurality of regulatory structural primitives with the same size.
[0044] In this step, if Figure 2 As shown, the component gradient model is modeled by Solidworks, and the printing path of the component gradient model is obtained by slicing software processing. When multiple identical structural primitive models are constructed by simulation software, the Hill function and impedance change function are used to obtain the change relationship between the thickness of different control structural primitives and the wave impedance value distribution, so as to construct the control structural primitive.
[0045] The Hill function and impedance change function of the control structure unit are:
[0046] f(x)=f(0)+R×(x h ) / (x h +K h )
[0047] Z(x)=k×ρ×C b ×[f(x)] 2
[0048] Where f(x) represents the Hill function of the regulated structural unit, x represents the thickness coordinate of the structural gradient material from the low-density end, f(0) represents the minimum radius of the tip of the actual prepared structural unit, R represents the range of regulated impedance change, K represents the proportional coefficient of the impedance change span, h represents the Hill coefficient of the regulated impedance change form, Z(x) represents the impedance change function at the position x thickness away from the initial layer, ρ represents the material density at the position x thickness away from the initial layer, C b represents the sound velocity at constant pressure at a position x thickness away from the initial layer, and k represents the proportional coefficient of impedance change.
[0049] Through the organic combination of the Hill function and the impedance change function, a quantitative relationship between structural parameters and performance was established. The Hill function realizes the continuous and controllable change of the structural element size by adjusting the Hill coefficient h, the proportional coefficient K and the R value. The impedance change function takes into account the influence of material density and sound velocity and realizes the precise regulation of impedance. This multi-parameter collaborative control method not only provides theoretical guidance for structural design and mathematical basis for performance prediction, but also has good parameter adjustability and engineering applicability.
[0050] In this embodiment, a gradient structure with a wide adjustable range of impedance change is obtained by regulating the gradient structure through mathematical expression, which solves the problem of single structure and limited adjustable range caused by regulating the structure through structural parameters. At the same time, the stress-strain rate data of the designed structure is directly obtained by using programming code and finite element simulation software based on mathematical expression, avoiding the high cost and low benefit of obtaining data by changing empirical structural parameters, and making it difficult to construct a structure-activity relationship between the structure and the controllable loading waveform and stress-strain rate.
[0051] In this embodiment, the regulating structural unit includes any one of polyurethane acrylic resin, polyester acrylic resin and amino acrylic resin, and the volume density of the regulating structural unit is 0-1.3 g / cm 3 By using polyurethane acrylic resin, polyester acrylic resin or amino acrylic resin as the structural element material, combined with 0-1.3g / cm 3 The controllable density range enables precise regulation of the performance of the structural elements; the selectivity of the three resin materials provides greater design freedom, while the wide density control range ensures a good match with the matrix material. It not only has excellent processing performance and molding characteristics, but also can meet the performance requirements of different application scenarios, providing a flexible and reliable material selection solution for the practical application of regulating structural elements.
[0052] Furthermore, the single-component disc is prepared by filling a resin-based composite material with metal particles of different contents, the particle size of the metal particles is 1 to 10 μm, the metal particles are copper particles, and the resin-based composite material is PMMA. The mass fraction of the copper particles is any one of 10wt.%, 25wt.%, 40wt.%, and 60wt.%, and the mass fraction of PMMA is any one of 90wt.%, 75wt.%, 60wt.%, and 40wt.%. The thickness of the single-component disc is 50 to 400 μm, and the density of the single-component disc is 1.3 to 4.5 g / cm 3 .
[0053] By adopting a multi-level ratio combination of copper particles with a particle size of 1 to 10 μm and PMMA resin-based composite materials, precise thickness control and density gradient regulation of single-component wafers are achieved. Micron-sized copper particles ensure good dispersibility and interface bonding, and the PMMA resin matrix provides excellent processing performance and coating properties. The multi-level ratio optimizes the interface stress distribution, which not only realizes the continuous and controllable change of material properties, but also has practical advantages such as controllable process flow, predictable performance, and reasonable cost, providing a feasible technical solution for the practical application of functional gradient materials.
[0054] In one example, the component gradient model includes five layers of single-component discs with different densities, and the multiple single-component discs are stacked in order from small to large density to obtain a component gradient model with uniformly increasing component density.
[0055] Step S2, arranging multiple regulatory structural primitives on the upper surface of the component gradient model in a preset arrangement to form a multi-component gradient structural model, wherein the cross-sectional area of the structural primitive model gradually increases from the direction away from the component gradient model toward the direction close to the component gradient model.
[0056] In this step, the multi-component gradient structure model is composed of a plurality of structural unit models with gradually increasing cross-sectional areas densely arranged on the upper surface of a component gradient model with a certain thickness and diameter. By changing the structure of the structural unit, the surface density distribution of the gradient structure is regulated, and then the wave impedance distribution of the gradient structure is regulated. The surface density gradient material is prepared in an integrated manner using additive manufacturing technology. The preparation accuracy is coordinated by controlling the thickness of the resin layer and the degree of polymerization to obtain a gradient structure with excellent interlayer bonding strength, low tip size, and no warping defects.
[0057] Step S3, based on printing parameters and 3D printing technology, preparing a multi-component gradient structure corresponding to the multi-component gradient structure model, wherein the printing parameters include single-component disc layer thickness, exposure intensity and printing speed.
[0058] In one example, the component gradient structure is first obtained by extruding PLA filaments through the nozzle of the FDM equipment (0.2mm, 0.4mm nozzle diameter), and the component gradient structure is moved to the SLA equipment by a robotic arm and then photocured to obtain a gradient structure densely packed on the component gradient structure. The component gradient structure is first obtained by hot pressing a mixed and mixed material with different Cu mass fractions to obtain a single-component disc with a single layer thickness of 50 to 400μm, and then the different single-component discs are stacked from small to large in density and linked by hot pressing to obtain a component gradient material with uniformly increased component density.
[0059] This step also includes steps S31 to S33.
[0060] Step S31, using FDM equipment to print the component gradient structure corresponding to the component gradient model, wherein the nozzle temperature of the FDM equipment is set to 200-230°, the printing speed of the FDM equipment is set to 25-40 mm, and the layer thickness of the single-component disc is set to 0.05-0.2 mm.
[0061] In this step, a multi-component gradient material is modeled by Solidworks, and the printing path of the component gradient model is obtained through slicing software processing. FDM equipment is used to extrude 1.75mm TPU and PLA filaments. The nozzle temperature is between 200 and 230 degrees Celsius, the layer thickness is set between 0.05 and 0.2mm, the platform temperature is set between 50 and 70 degrees Celsius, and the printing speed is between 25 and 40mm.
[0062] Step S32, using an SLA device to print a structural gradient corresponding to the structural gradient model on the upper surface of the component gradient structure, wherein the light wavelength used by the SLA device is 355nm, the layer thickness of the SLA device is set to 0.01-0.05mm, and the exposure intensity of the SLA device is set to 20-100mW / cm 2 .
[0063] In this step, the component gradient model with a density of 1.1 to 1.3 is clamped to the center of the working area of the SLA device by the robotic arm. The robotic arm sends a signal, and the SLA device receives the signal to continue printing the structural gradient model on the component gradient model. The material used by the SLA device is acrylic material, the light wavelength of the SLA device is 355nm, the layer thickness is set to 0.01 to 0.05mm, and the light intensity is 20 to 100mW / cm 2 , exposure time is 0.1~2s.
[0064] Further, 10wt.% Cu particles (25wt.%, 40wt.%, 60wt.%) and 90wt.% (75wt.%, 60wt.%, 40wt.%) PMMA are placed in an internal mixer at 200-230°C and a rotation speed of 60-40r / min for 10-30min. The higher the metal particle content, the higher the temperature setting, the slower the rotation speed, and the longer the internal mixing time. The materials with different contents of metal particles obtained by internal mixing are hot pressed respectively, and the materials are heated to between 175 and 200°C to make them in a flowable state. The pressure of the upper and lower pressing plates is set to 5-20MPa by the hot press, and the single-component disc with a layer thickness of 70-150 microns is obtained by heat preservation and pressure hot pressing for 20-30min under constant pressure. The single-component discs with several different component contents are hot pressed from low to high metal content to form a component gradient structure.
[0065] The circular plate of the structural gradient material obtained by additive manufacturing is connected to the end with the lowest metal content of the component gradient material obtained by hot pressing, and is bonded with epoxy resin AB glue. The two are connected with AB glue and placed in an environment of 30 to 50 degrees Celsius for 1 to 3 hours to complete the connection and obtain a multi-component gradient structure.
[0066] In this embodiment, high-quality preparation of composite materials with different metal contents is achieved by precisely controlling the internal mixing process parameters and the hot pressing process parameters. The higher the metal content, the higher the temperature, the lower the rotation speed and the longer the internal mixing time to ensure the uniformity of the material. At the same time, single-component wafers with a thickness of microns are obtained by hot pressing and the construction of component gradient structures is realized. Epoxy resin AB glue is then used to reliably connect the structural gradient material with the component gradient material, forming a multi-component gradient structure with controllable performance and stable structure. Combined hot pressing, melt deposition and photocuring technology are used to obtain a multi-component gradient structural material with zero initial impedance, a wide range and uniform transition. While ensuring an extremely weak initial impact, the problem of a single structural gradient material and a narrow density range is solved, and a multi-component gradient material with a uniform transition in density from 0 to 4.5 is realized.
[0067] Step S33: clean the prepared multi-component gradient structure and place it under a light intensity of 60 to 80 mW / cm 2 The secondary curing is completed by irradiating in a curing box for 15 to 30 minutes.
[0068] Through the design of single-component discs with different densities in the component gradient model and the reasonable configuration of regulatory structural elements of consistent size in the structural gradient model, dual gradient regulation of material components and structural properties is achieved, which solves the problems of single structure and limited controllable range caused by regulating the structure through structural parameters, thereby improving the impedance control range of the structural gradient material. At the same time, the gradual design of the cross-sectional area of the structural element effectively improves the stress concentration phenomenon and improves the mechanical properties and stability of the structure. By precisely controlling 3D printing parameters such as layer thickness, exposure intensity and printing speed, the molding quality and manufacturing efficiency are ensured, and the material interface bonding strength is enhanced.
[0069] See also Figure 3 , Figure 3 Schematic diagram of different mathematical function controls for controlling the impedance change range, the Hill coefficient for controlling the impedance change form, and the proportional coefficient of the impedance change span.
[0070] Please continue reading Figure 4 and Figure 5 , which are four multi-dimensional arrangements for achieving controllable stress-strain rate, and schematic diagrams of the regulation effects corresponding to the above four multi-dimensional arrangements.
[0071] See also Figure 6 , Figure 6 The impedance change trend diagram under different mass percentage (wt%) conditions is shown. The horizontal axis in the figure represents the different concentration conditions from the comparative example to 60wt%, and the vertical axis represents the impedance value, with the unit of *10 6 kg / m 2·s. From the data, it can be seen that the impedance value shows a clear upward trend with the increase of wt%. Under the comparative conditions, the impedance is 3.4, which rises to 6.3 at 10wt%, reaches 7.8 at 25wt%, increases to 9.2 at 40wt%, and reaches the highest value of 11.1 at 60wt%. Figure 6 The data points are connected by slashes, which intuitively show the gradual change of impedance with increasing concentration and reflect the continuous change characteristics of material properties.
[0072] like Figure 7 As shown, Figure 7 The microstructure and structural characteristics of multi-component structural gradient materials are demonstrated. Figure 7 (A) in the figure shows, from left to right, a pyramid-shaped microstructure with a gradient structure, a step-shaped structure with an interlayer spacing ranging from 39 to 41 μm, and a regular hexagonal concentric ring structure with a central area size of 41.2 μm. Figure 7 The circular cross-sectional image on the left in (B) shows the layered structure of different regions through three dotted lines (a, b, c), and the three columnar structure images on the right (a, b, c) show the gradient change of the material from low density to high density.
[0073] like Figure 8 As shown, Figure 8 The tensile strength curve is shown in Figure 2. The curve of Example 2 is the highest, with a maximum stress of about 55 MPa, showing the best mechanical properties. The curve of Example 1 is below Example 2, with a maximum stress of about 45 MPa, and the performance is second. The curve of the comparative example is the lowest, with a maximum stress of about 30 MPa, showing the worst mechanical properties. All curves show linear growth in the initial stage. As the strain increases, the curve enters the nonlinear region, showing plastic deformation. In the final stage, all samples break when the strain is close to 20-25%.
[0074] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a multi-component structural gradient material, characterized in that: The method comprises: Constructing a component gradient model and a structural gradient model by simulation software, wherein the component gradient model includes a plurality of single-component discs with different densities, and the structural gradient model includes a plurality of regulatory structural primitives with the same size; Arranging a plurality of the regulatory structural primitives in a preset arrangement on the upper surface of the component gradient model to form a multi-component gradient structural model, wherein the cross-sectional area of the structural primitive model gradually increases from a direction away from the component gradient model toward a direction close to the component gradient model; Based on printing parameters and 3D printing technology, a multi-component gradient structure corresponding to the multi-component gradient structure model is prepared, wherein the printing parameters include the single-component disc layer thickness, exposure intensity and printing speed.
2. The method for preparing a multi-component structural gradient material according to claim 1, characterized in that: Based on printing parameters and 3D printing technology, a multi-component gradient structure corresponding to the multi-component gradient structure model is prepared, specifically including: Using an FDM device to print a component gradient structure corresponding to the component gradient model, wherein the nozzle temperature of the FDM device is set to 200-230°, the printing speed of the FDM device is set to 25-40 mm, and the layer thickness of the single-component disc is set to 0.05-0.2 mm; The structure gradient corresponding to the structure gradient model is printed on the upper surface of the component gradient structure by using an SLA device, wherein the light wavelength used by the SLA device is 355nm, the layer thickness of the printing of the SLA device is set to 0.01-0.05mm, and the exposure intensity of the SLA device is set to 20-100mW / cm 2 ; The prepared multi-component gradient structure was cleaned and placed under a light intensity of 60-80 mW / cm 2 The secondary curing is completed by irradiating in a curing box for 15 to 30 minutes.
3. The method for preparing a multi-component structural gradient material according to claim 1, characterized in that: The Hill function and impedance change function of the control structure primitive are respectively: f(x)=f(0)+R×(x h ) / (x h +K h ) Z(x)=k×ρ×C b ×[f(x)] 2 Wherein, f(x) represents the Hill function of the control structure unit, x represents the thickness coordinate of the structure gradient material from the low-density end, f(0) represents the minimum radius of the tip of the actual prepared structure unit, R represents the control impedance change range, K represents the proportional coefficient of the impedance change span, h represents the Hill coefficient of the control impedance change form, Z(x) represents the impedance change function at the position x thickness from the initial layer, ρ represents the material density at the position x thickness from the initial layer, C b represents the sound velocity at constant pressure at a position x thickness away from the initial layer, and k represents the proportional coefficient of impedance change.
4. The method for preparing a multi-component structural gradient material according to claim 1, characterized in that: The single-component disc is prepared by filling a resin-based composite material with metal particles of different contents, and the particle size of the metal particles is 1 to 10 μm.
5. The method for preparing a multi-component structural gradient material according to claim 4, characterized in that: The metal particles are copper particles, and the resin-based composite material is PMMA.
6. A method for preparing a multi-component structural gradient material according to claim 5, characterized in that: The mass fraction of the copper particles is any one of 10wt.%, 25wt.%, 40wt.% and 60wt.%, and the mass fraction of the PMMA is any one of 90wt.%, 75wt.%, 60wt.% and 40wt.%.
7. The method for preparing a multi-component structural gradient material according to claim 1, characterized in that: The thickness of the single-component disc is 50-400 μm, and the density of the single-component disc is 1.3-4.5 g / cm 3 .
8. The method for preparing a multi-component structural gradient material according to claim 1, characterized in that: The component gradient model includes five layers of single-component discs with different densities, and a plurality of the single-component discs are stacked in order from small to large density to obtain a component gradient model with uniformly increasing component density.
9. The method for preparing a multi-component structural gradient material according to claim 1, characterized in that: The regulatory structural unit comprises any one of polyurethane acrylic resin, polyester acrylic resin and amino acrylic resin, and the volume density of the regulatory structural unit is 0 to 1.3 g / cm 3 .
10. The gradient structure of the multi-component structural gradient material obtained by the preparation method as described in any one of claims 1 to 9.
Citation Information
Patent Citations
Piezoelectric transducer array-based non-baseline data plane stress field on-line monitoring method, system and equipment, and medium
CN114459649A
Metal / polymer gradient acoustic impedance matching layer and preparation method and application thereof
CN115319988A
Functional gradient multi-scale thermal metamaterial design method for additive manufacturing
CN116417098A
Al-Ag controllable loading functional gradient composite material and preparation method thereof
CN117698225A
Gradient structure for realizing controllable stress-strain rate loading and preparation method
CN118269354A